Chronic granulomatous disease associated with common variable immunodeficiency - 2 clinical cases - Pacheco, C (2014)
INTRODUCTION: Chronic granulomatous disease associated with common variable immunodeficiency (GD-CVID), although well documented, is rare. Granulomatous lesions can affect several organs and are histologically indistinguishable from sarcoidosis. CLINICAL CASES: Case 1: A 39-year-old male patient with CVID, asymptomatic although with thrombocytopenia and mediastinal-hilar adenopathies. GD-CVID was diagnosed by bone marrow biopsy. Progressive clinical and radiological improvement was obtained with corticotherapy. Case 2: A 38-year-old male patient with CVID, suffered from asthenia, anorexia, myalgia, lower limbs edemas, and dry cough. He had mediastinal and bilateral hilar adenopathies within which biopsy revealed non-necrotizing granulomatous infiltrate. A spontaneous resolution was detected after 9 months of evolution. CONCLUSION: GD-CVID is rare and can mimetize other pathologies, namely, sarcoidosis; it should therefore be publicized and discussed so that it becomes a general clinical knowledge.